IMPLEMENTATION THROUGH ONLINE GAME RENTAL SITES PHP AND MYSQL PROGRAMMING - Melani Dewi Lusita (JAKSTIK Journal, 2006)
The rapid development of the computer becomes a facilitator for information. The Internet is one way to get information. With the Internet one can obtain accurate information in order without spending a lot of cost. In addition, the Internet also can be used as a means of promotion. This site is created as a promotional tool for owners of rental online game and as a medium of information and means of interaction among visitors.